Periodization and block periodization in sports: emphasis on strength-power training-a provocative and challenging narrative - Stone, M. H.; Hornsby, W. G.; Haff, G. G.; Fry, A. C.; Suarez, D. G.; Liu, J.; Gonzalez-Rave, J. M.; Pierce, K. C. (The Journal of Strength and Conditioning Research, 2021)
Periodization can be defined as a logical sequential, phasic method of manipulating fitness and recovery phases to increase the potential for achieving specific performance goals while minimizing the potential for nonfunctional over-reaching, overtraining, and injury. Periodization deals with the micromanagement of timelines and fitness phases and is cyclic in nature. On the other hand, programming deals with the micromanagement of the training process and deals with exercise selection, volume, intensity, etc. Evidence indicates that a periodized training process coupled with appropriate programming can produce superior athletic enhancement compared with nonperiodized process. There are 2 models of periodization, traditional and block. Traditional can take different forms (i.e., reverse). Block periodization has 2 subtypes, single goal or factor (individual sports) and multiple goals or factors (team sports). Both models have strengths and weaknesses but can be "tailored" through creative programming to produce excellent results for specific sports.